Quantifying depletion rates of benthic macrofauna from the Danish Seine – A ‘low impact’ mobile bottom-contacting fishing gear - Katrina Bromhall; Ciarán McLaverty; Ole R. Eigaard; Tim J.G. Wilms; Thomas Noack; Finbarr G. O’Neill; Grete E. Dinesen (Fisheries Research, 2026)

Factors influencing the abundance of European green crab Carcinus maenas: combined effects of temperature, habitat and predator release - Mikkel Steen Nielsen; Jon C. Svendsen; Tim Wilms; Jeannet L. Bertelsen; Bo Mammen Kruse; Martin Lindegren (Estuarine, Coastal and Shelf Science, 2025)

Fish aggregations at oil and gas platform foundations in the North Sea - Bruno Ibanez‐Erquiaga; Henrik Baktoft; Tim Wilms; Tobias Karl Mildenberger; Jon Christian Svendsen (Fisheries Management and Ecology, 2024)
Globally, aging offshore oil and gas (O&G) platforms face resource depletion, and regulations often demand platform removal through decommissioning. In the North Sea, >€90 billion will be needed for decommissioning by 2060. However, the influence of O&G platforms on fish communities is poorly understood. This challenges predictions of possible fisheries scenarios associated with different decommissioning options. Here, we examined the role that North Sea platforms played on fish communities. We explored patterns of fish abundance and body size variation along transects from O&G platforms comparing catch per unit effort data. Fish abundance was positively associated with O&G platforms. Atlantic cod, plaice, saithe, and mackerel were most abundant near platforms. Similarly, larger Atlantic cod were near the O&G platforms. Our study provided information for decision‐making regarding platform decommissioning scenarios by evidencing O&G platform habitat provisioning for various commercial fish species.